Evaluation and identification of Wild Species promising for diseases of Sesame: Evaluation and identification of Wild Species promising for diseases of Sesame - M G PALAKSHAPPA; HARSHIYA BANU; S G PARMESHWARAPPA; LAXMI C PATIL; VANISHREE (Journal of Oilseeds Research, 2020)
Ten wild species accessions were screened during Summer 2016-17 for diseases, all wild accessions were found promising for phytoplasma except IC 0208679, IC 0208660 and IC 208664A. All tested accessions were found promising for powdery mildew except IC 0204206. During kharif 2018-19, all lines evaluated have recorded moderately susceptible (IC 0204206, IC 0208660, IC 0208661, IC 0208662, IC 0208663, IC 208679, IC 0208681) to susceptible reaction to Cercospora leaf spot. Minimum incidence of phytoplasma (13.3 %) was observed in IC 208664A and maximum phytoplasma observed was 42.1 % in IC 0204206. All wild accessions were susceptible to bacterial and Cercospora leaf spot exhibiting highly reaction over the years.